Lung cancer risk in professional drivers in Korea: A population‐based proportionate cancer incidence ratio study. Issue 4 (31st October 2015) - Koh, Dong‐Hee; Kong, Hyun‐Joo; Oh, Chang‐Mo; Jung, Kyu‐Won; Park, Donguk; Won, Young‐Joo
Abstract : Lung cancer risk in professional drivers in Korea: A population‐based proportionate cancer incidence ratio study: Dong‐Hee Koh, et al . Department of Occupational and Environmental Medicine, International St. Mary's Hospital, Catholic Kwandong University, Republic of Korea Objective: Professional drivers are exposed to diesel engine exhaust and outdoor air pollution while driving. Diesel engine exhaust and outdoor air pollution are known carcinogens causing lung cancer. However, previous epidemiological studies examining lung cancer risk in professional drivers have not shown a consistent association. In the present study, we evaluated lung cancer risk among Korean professional drivers. Methods: Subjects consisted of male drivers aged 30–59 registered in the Korea Central Cancer Registry for lung cancer between 1999 and 2011. Proportionate cancer incidence ratios (PCIRs) for lung cancer were calculated and indirectly age standardized with the male general population. Additional PCIRs were calculated by indirectly adjusting for the effect of cigarette smoking. Results: The PCIR for lung cancer in professional drivers during the study period increased significantly (1.20, 95% CI: 1.13−1.26). The increased risk was generally consistent throughout study years and age categories. Adjusting for the effect of cigarette smoking did not change the significance of the associations (1.09, 95% CI: 1.03−1.15). Conclusions: Our findings support an association between lung cancer and driver jobs in the Korean male population. However, the association should be further evaluated in a study with a longitudinal design and a quantitative exposure assessment.